A New Surgical Approach for the Treatment of Conjunctivochalasis: Reduction of the Conjunctival Fold with Bipolar Electrocautery Forceps - Eduardo Arenas; Diana Muñoz (The Scientific World Journal)
Aim. To report a new surgical technique for the treatment of conjunctivochalasis. Methods. A new surgical technique in which specially designed bipolar electrocautery forceps facilitate the complete reduction of the conjunctival folds without creating lesions near the corneoscleral limbus was designed. A retrospective revision of the medical records of patients treated with this technique between the years 2011 and 2013 was made, and eighteen eyes of sixteen patients with conjunctivochalasis treated with this new technique were included. Results. All the eyes treated showed a significant improvement with no evidence of scar lesions after a mean follow-up time of 10 months. Conclusions. The surgical technique presented here could be a good alternative for the management of conjunctivochalasis.